The administration of a loading dose of aspirin to patients presenting with acute myocardial infarction while receiving chronic aspirin treatment reduces thromboxane A2-dependent platelet reactivity. (June 2014) - Santos, Maria Teresa; Madrid, Isabel; Moscardo, Antonio; Latorre, Ana M.; Bonastre, Juan; Ruano, Miguel; Valles, Juana
Abstract The optimal dose of aspirin for patients presenting with acute myocardial infarction (AMI) while receiving chronic aspirin therapy has not been clearly established. We evaluated whether continued treatment with 100 mg of aspirin or a loading dose (200–500 mg) influences thromboxane A2 (TX) suppression or platelet reactivity. Sixty-four consecutive patients with AMI and 98 healthy subjects (82 aspirin-free and 16 receiving 100 mg daily for a week) were evaluated. Treatment was at the discretion of the attending physician. Collagen (1 µg/ml)-induced TX synthesis, 14C-serotonin-release, platelet aggregation, and the PFA-100 assay were evaluated. The platelet TX synthesis of patients receiving a loading dose of aspirin was sixfold lower than that of patients receiving 100 mg of aspirin (p < 0.005). This was associated with marked reductions in 14C-serotonin-release and arachidonic-acid-induced aggregation and an increase in the PFA-100 closure time (p < 0.01). Categorization of patients according to their TX synthesis (<95% or ≥95% inhibition vs. healthy aspirin-free subjects) revealed that 8% of the patients treated with loading doses had a poor response (<95% inhibition) vs. 53% of those treated with 100 mg (p < 0.001). Patients with lower TX inhibition had higher serum NT-Pro-BNP (p < 0.005), a marker of poor left ventricular systolic function. Administration of a loading dose of aspirin to patients with AMI during existing chronic aspirin treatment induced greater reductions in platelet TX synthesis and TX-dependent platelet reactivity than the continued treatment alone.